Autonomy, Self-determination, and Human Rights: Legal Safeguards in Argentina to Prevent Elder Abuse and Neglect. (4th January 2018) - Isolina Dabove, María
Abstract: Elder abuse and neglect is one of the most important social problems in the world and it has grown together with global ageing. In this research, we analyse the meaning of elder abuse and its relationship to personal autonomy. After that, we study the scope and content of the Argentinean and Inter-American legal institutions presently in force designed to empower older people and prevent this problem. Fortunately, Argentinian Law and the new Inter-American Convention recognize some strong instruments to prevent elder abuse, promote personal autonomy, and the empowerment of the elderly in dependency situations. The first steps have been taken.